Anaesthetic Challenges in Minimally Invasive Gastric Pull-Up for Oesophageal Atresia With Significant Proximal-Distal Oesophageal Discrepancy in an Infant - a Comprehensive Case Report - Richhariya, Dr.Suruchi; Shikha,; Preeti, Preeti; Dr.Zainab,; Vaishali,; Sharma, Pramod K; Harish,; Kumar, Sandeep (Scripta Medica, 2025)
A unique subset of infants diagnosed with oesophageal atresia (EA) with tracheooesophageal fistula (TEF) are those born with pure long-gap oesophageal atresia (LGEA), constituting around 10 % of oesophageal atresia. Several procedures have been developed for oesophageal reconstruction and gastric pull-up has demonstrated promising outcomes. Anaesthetic management for the gastric pull-up surgery is challenging with a high risk of respiratory distress and a high incidence of perioperative tachyarrhythmias. Case of infant diagnosed with LGEA, marked by a significant proximal-distal oesophageal discrepancy, initially underwent cervical oesophagostomy and feeding gastrostomy in the neonatal period is presented. Anaesthetic challenges were faced both intraoperatively and postoperatively.